Effect of ricinol-2-oxazoline methylmaleate on the structure and properties of polyamide 6 and low density polyethylene blends - Jeziórska, R. (Polimery, 2022)
Effect of PE-LD grafting with ricinol-2-oxazoline methylmaleate (MRO) on phase structure as well as thermal and mechanical properties of polyamide 6 and low-density polyethylene blends (PA 6/PE-LD-g-MRO), differing in composition, obtained in reactive extrusion process, has been studied. This effect was studied using the following methods: infrared spcctroscopy (FT-IR, Fig. 1 and 2), differential scanning calorimetry (DSC, Fig. 3 and 4, Table 1 and 2), scanning electron microscopy (SEM, Fig. 5) and dynamic mechanical/thermal analysis (DMTA, Figs. 6-10). The blends show heterogenic structure which, as a result of chemical reactions going during the extrusion, stabilizes at microphase level [probably of functional groups of PA 6 with oxazoline groups grafted onto PE according to equation (2)]. It advantageously influences mechanical properties (Tables 3-5, Fig. 11). Results of investigations show the compatibilizing effect of MRO.